Efektivitas Informasi Multimedia Video (Video Dan Lisan) untuk Menurunkan Tingkat Kecemasan Praanestesi Umum pada Pasien yang akan Dilakukan Tindakan Operasi Elektif dengan Anestesi Umum Teknik Intubasi - Budianti, Nugrahaeni; Pratomo, Bhirowo Yudo; Rahardjo, Sri (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2018)
Background. Preoperative anxiety is a problem faced by two-thirds patients who would undergo surgery.Anxiety can not be handled properly, will cause adverse pathophysiologic responses. General anesthesiaintubation techniques as one of the anesthetic techniques often lead to an increase in preoperative anxiety. To reduce the level of preoperative anxiety, we can give preoperative information. The health information provided can be well understood by patients and can be used to reduce anxiety situation experienced by the patients. Methods. This studied was Randomized Controlled Trial (RCT). Subjects were patients undergone elective surgery general anesthesia using intubation techniques. The subjects were 110 patients that divided into two groups: the video group and the verbal group. The verbal group received preoperative information verbally, while the video group received preoperative information through a video of general anesthesia intubation technique procedures. The measurement of anxiety level was measured four times, once before the treatment (the level of anxiety/ LA-1) and three times after the treatment, namely when in the ward (LA-2), when in the surgical installation acceptance (LA-3) and when in the operating room prior to general anesthesia intubation techniques (LA-4). The assessment of anxiety used Spielberger State-Trait Anxiety Inventory (STAI) questionnaire of Y-1 form.Results. The percentage of anxiety reduction in video group was bigger than in Verbal group at all measurement times in TK-2 group of 40% video and verbal group 12,7%, in TK-3 video group 41,8% and verbal group 12,7% and at TK-4 video group 41.8% and verbal group 10.9%. Statistically different in the anxiety level between video group and verbal group were obtained in LA-2, LA-3 and LA-4 (p = 0.001, p = 0.001 and p = 0.000).Conclusion. Multimedia video information (video and verbal) is more effective in reducing preanesthesia anxiety levels in patients undergoing elective surgery with general anesthesia of intubation techniques when compared with verbal information.